608 Comparison of topical treatment of cervical squamous intraepithelial lesionswith imiquimod with standard excisional technique using LLETZ: a randomized controlled trial. (14th December 2020) - Cokan, Andrej; Pakiž, Maja; Knez, Jure; Dovnik, Andraž; Kodrič, Tatjana; Mahdawi, Leyla Al; Serdinšek, Tamara; Fokter, Alenka Repše; But, Igor
Abstract : Introduction/Background: Standard treatment of cervical squamous intraepithelial lesions (SIL) is large loop excision of transformation zone (LLETZ), which is associated with increased risk of preterm delivery, higher subfertility rate, and higher spontaneous abortions rate. Our aim was to determine whether topical treatment of high-grade SIL (HSIL) with imiquimod is comparable to standard treatment in terms of efficiency and side effects occurrence. Methodology: We performed a randomized controlled study. Patients with HSIL aged 18–40 years were included and treated with either imiquimod, 3 times per week for 16 weeks (experimental arm), or with LLETZ (control arm). Treatment success was evaluated by regression to low-grade SIL (LSIL) 20 weeks after initiation of the treatment in the experimental arm and by negative cytology 6 months after LLETZ in the control arm. Secondary outcome was occurrence of the side effects during and after treatment. Statistical analysis was performed using SPSS Statistics Programme. Statistical significance was set at p-value<0.05. Results: We included 104 patients. In the experimental arm, 43 out of 52 patients (82.7%) completed treatment, while in the control arm, all of the 52 patients received the planned treatment (100%). Treatment with imiquimod was successful in 62.8% and treatment with LLETZ in 75.0%, the difference was not statistically significant (p-value=0.288). When evaluating treatment success in the intermediate risk subgroup (patients with cervical intraepithelial neoplasia grade 2 – CIN 2), there were also no statistically significant differences between groups (p-value=0.366). However, LLETZ was significantly more successful in patients with CIN 3 lesions (p-value=0.012). We did not observe any cases of progression of the precancerous disease to cancer. Side effects and severe side effects were significantly more prevalent in the imiquimod than in the LLETZ group (88.5% vs. 44.2% (p-value<0.001) and 51.9% vs. 13.5% (p-value<0.001), respectively). The most prevalent side effects were vaginal inflammation, flu-like and lower urinary tract symptoms. Over the course of the treatment with imiquimod, overall occurrence and the severity of side effects decreased. Conclusion: Topical imiquimod has a potential of becoming an alternative treatment for HSIL, especially in younger women with intermediate risk HSIL. However, its use is associated with higher occurrence of side effects, which can affect patients' quality of life. In the future, larger studies evaluating the long-term effects of this treatment are needed, especially in the view of disease progression and recurrence. Disclosures: The authors declare no competing interests. This research was financially supported by UMC Maribor.